A Review of African Swine Fever and the Potential for Introduction into the United States and the Possibility of Subsequent Establishment in Feral Swine and Native Ticks - Brown, Vienna R.; Bevins, Sarah N. (Frontiers in Veterinary Science, 2018)
African swine fever (ASF) is caused by African swine fever virus (ASFV) which can cause substantial morbidity and mortality events in swine. The virus can be transmitted via direct and indirect contact with infected swine, their products or via competent vector species, especially Ornithodoros ticks. Africa and much of Eastern Europe are endemic for ASF; a viral introduction to countries that are currently ASF-free could have severe economic consequences due to the loss of production from infected animals and the trade restrictions that would likely be imposed as a result of an outbreak. We identified vulnerabilities that could lead to ASFV introduction or persistence in the United States or other ASF-free regions. Both legal and illegal movement of live animals, as well as the importation of animal products, byproducts, and animal feed, pose a risk of virus introduction. Each route is described and current regulations designed to prevent ASFV and other pathogens from entering the United States are outlined. Furthermore, existing ASFV research gaps are highlighted. Laboratory experiments to evaluate multiple species of Ornithodoros ticks that have yet to be characterized would be useful to understand vector competence, host preferences, and distribution of competent soft tick vectors in relation to high pig production areas as well as regions with high feral swine (wild boar or similar) densities. Knowledge relative to antigenic viral proteins that contribute to host response and determination of immune mechanisms that lead to protection are foundational in the quest for a vaccine. Finally, sampling of illegally imported and confiscated wild suid products for ASFV could shed light on the types of products being imported and provide a more informed perspective relative to the risk of ASFV importation.